2016
DOI: 10.1007/s40615-016-0280-6
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring Willingness to Participate in Clinical Trials by Ethnicity

Abstract: African-Americans and Hispanic-Americans are disproportionately affected by cancer, yet underrepresented in cancer clinical trials. Because of this, it is important to understand how attitudes and beliefs about clinical trials vary by ethnicity. A national, random sample of 860 adults was given an online survey about attitudes toward clinical trials. We examined willingness to participate in clinical trials, attitudes toward clinical trials, trust in doctors, attitudes toward alternative and complementary medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 30 publications
0
48
0
1
Order By: Relevance
“…Despite low levels of engagement, the poll also found that 56% of Hispanics said that the opportunity to improve the health of others is a very important reason to take part in a clinical trial and 81% said that they would likely participate in a clinical trial if recommended by a doctor (Research!America, ). Lack of trust has been cited as a major factor in lack of participation in clinical trials among Hispanics (Arevalo et al, ; Byrne, Tannenbaum, Glück, Hurley, & Antoni, ; Pariera, Murphy, Meng, & McLaughlin, ). However, some researchers have found that low participation in cancer clinical trials among non‐English–speaking Hispanics may be related to lack of information and language barriers, not lack of willingness to participate in research (Arevalo et al, ; Bryne et al, ; Nodora, Nuño, O'Day, Yrun, & Garcia, ; Pariera et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite low levels of engagement, the poll also found that 56% of Hispanics said that the opportunity to improve the health of others is a very important reason to take part in a clinical trial and 81% said that they would likely participate in a clinical trial if recommended by a doctor (Research!America, ). Lack of trust has been cited as a major factor in lack of participation in clinical trials among Hispanics (Arevalo et al, ; Byrne, Tannenbaum, Glück, Hurley, & Antoni, ; Pariera, Murphy, Meng, & McLaughlin, ). However, some researchers have found that low participation in cancer clinical trials among non‐English–speaking Hispanics may be related to lack of information and language barriers, not lack of willingness to participate in research (Arevalo et al, ; Bryne et al, ; Nodora, Nuño, O'Day, Yrun, & Garcia, ; Pariera et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 There are multiple reasons minorities have been underrepresented in intervention studies. 12,13 For example, in the black community, there is a long documented history of a distrust of research and the health care system. 13,14 Research that includes a sufficient number of ethnic minority cancer survivor populations is crucial to addressing the disparities in health outcomes observed across race, ethnicity, and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…44 Respondents were less likely to be recruited to a study if they were black or if they were classified as middle income. 44 Several other studies have also shown that patient age, 45 education level, 46 and ethnicity 47 influence likelihood of enrollment. Our study collected demographic data but was unable to look specifically at subgroups because of low response rates.…”
Section: Demographic Factors Influencing Participationmentioning
confidence: 94%